Shaping rights in the ECHR : the role of the European Court of Human Rights in determining the scope of human rights - Brems, Eva; Gerards, Janneke (Cambridge University Press, 2013)
"In fundamental rights adjudication, a court first has to determine whether the interest at stake falls within the scope of the fundamental right invoked. Whether or not an individual interest falls within the scope or ambit of one of the fundamental rights protected by the European Convention on Human Rights determines whether or not the European Court of Human Rights can decide on the merits of a case. This volume brings together a variety of legal scholars in order to examine the scope of fundamental rights. Topics range from the nature of human rights and the real or imagined risk of rights inflation to theories of positive obligations and social and economic rights. It contains contributions of a theoretical nature as well as analytical overviews of the ECtHR's approach. In addition, comparisons are made with domestic, EU and international law"--